Recombinational DNA Repair in Cancer and Normal Cells: The Challenge of Functional Analysis. Issue 2 (10th December 2002) - Willers, Henning; Xia, Fen; Powell, Simon N.
Abstract : A major goal of current cancer research is to understand the functional consequences of mutations in recombinational DNA repair genes. The introduction of artificial recombination substrates into living cells has evolved into a powerful tool to perform functional analysis of DNA double strand break (DSB) repair. Here, we review the principles and practice of current plasmid assays with regard to the two major DSB repair pathways, homologous recombination and nonhomologous end-joining. A spectrum of assay types is available to assess repair in a wide variety of cell lines. However, several technical challenges still need to be overcome. Understanding the alterations of DSB repair in cancers will ultimately provide a rational basis for drug design that may selectively sensitize tumor cells to ionizing radiation and chemotherapy, thereby achieving therapeutic gain.